Wang, C. & Zheng, B. (Eds.). (2021). Empirical Studies of Translation and Interpreting: The Post-Structuralist Approach. Routledge. (pp. 285) https://doi.org/10.4324/9781003017400 - Shang, Wenbo (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
Book review